2020
DOI: 10.3390/agriculture10080348
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Yield Estimation and Its Components: A Linear Regression Approach

Abstract: Soybean yield estimation is either based on yield monitors or agro-meteorological and satellite imagery data, but they present several limiting factors regarding on-farm decision level. Aware that machine learning approaches have been largely applied to estimate soybean yield and the availability of data regarding soybean yield and its components (number of grains (NG) and thousand grains weight (TGW)), there is an opportunity to study their relationships. The objective was to explore the relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 82 publications
1
17
0
Order By: Relevance
“…R 2 = 0.67) model. These results are similar to linear multiple regression for soybean yield prediction using yield components (R 2 = 0.70) [43]. However, the Lasso variable selection provides a more practical use as only NDVI and FGCC measurements are necessary with a relatively negligible Adj.…”
Section: Resultssupporting
confidence: 75%
“…R 2 = 0.67) model. These results are similar to linear multiple regression for soybean yield prediction using yield components (R 2 = 0.70) [43]. However, the Lasso variable selection provides a more practical use as only NDVI and FGCC measurements are necessary with a relatively negligible Adj.…”
Section: Resultssupporting
confidence: 75%
“…According to Wei and Molin (2020), the linear regression models, based on the 1 000-seed weight and the number of seeds per soybean pod, demonstrated low (r = 0.50) and high (r = 0.92), respectively, linear correlations with the seed yield. In the present research, the values were considerably lower, especially for the 1 000-seed weight (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Among all the tested yield component traits in this study, NP showed the second-highest linear correlation with total seed yield and showed a positive correlation with PP. Many studies reported that the variations in the number of nodes per plant is usually accounted for the changes in the number of pods per plant [ 81 84 ]. A negative correlation between the total soybean seed yield and NRNP was found in this study.…”
Section: Discussionmentioning
confidence: 99%